MAGNETIC FIELD CONTROL OF THE LOW-TEMPERATURE MAGNETIC PROPERTIES OF STOICHIOMETRIC AND CATION-DEFICIENT MAGNETITE - Smirnov A.V.; Tarduno J.A. (My University, 2002)
We report three new types of low-temperature (<120 K) magnetic behavior from oxidized and stoichiometric pseudo-single domain magnetite: (1) a non-monotonic dependence of the saturation remanence to saturation magnetization ratio on the magnetic field (0-1.7 T) applied during cooling, (2) an induced magnetic anisotropy at temperatures below the transition from cubic to monoclinic crystalline symmetry at ~120 K (the Verwey transition) after cooling in magnetic fields between 0.01 and 0.09 T, and (3) a non-monotonic dependence of a low-temperature (10 K) remanent magnetization on the magnetic field (0.01-2.5 T range) applied during cooling through the Verwey transition. We interpret these phenomena in terms of relationships between crystal twins, that can form in monoclinic magnetite, and the reorganization of magnetic domains. Our results are important for interpretations of low-temperature magnetic measurements and provide new insight into the fundamental magnetic properties of magnetite at low temperatures.
Keywords: MAGNETITE; CRYSTAL SYSTEMS; MAGNETIC HYSTERESIS; TWINNING